An integrated perspective of humanism and supernaturalism for education: C. S. Lewis’s version of education - Lee, Seung Chun (Springer, 2013)
This paper explores some theoretical reflections on the connection between C. S. Lewis’s thoughts on the purpose and process of education and his understanding of supernatural human nature which has been relatively little explored. An introduction about Lewis’s career as a college teacher blends into the background of this paper. It is followed by Lewis’ argument on the purpose of education which is: To produce a ‘‘good man’’ (‘‘human’’) who pursues knowledge for the sake of learning and makes the right emotional and behavioural responses, affirming truly objective and universal values (Tao). Intertwined with this argument is the dual reality of the human condition straddling this world and the other one with the latter taking precedence over the former. In order to produce educated men and women, Lewis argues for making the most of literary experiences and liberal studies as a main avenue toward the transformation of the inner self of each student. These literary experiences need to be combined with a healthy dose of the right action and behaviour because deliberate action with a purpose can create a reality in our character through the process of gaining momentum as a real interest or attitude in that direction takes hold. Lastly, some of the implications of these reflections for those who work with the young in schools and in liberal education are drawn out.